65.2k views
0 votes
Match each expression to another expression with the same value. 24 ÷ 3 53 × 7 56 − 21 4 − 3 40 × 2 8 × 50 8 × (5 × 12 − 10) (8 × 7 − 3) × 7 8 × 3 ÷ (6 − 3)

User Khandpur
by
6.5k points

1 Answer

3 votes

Answer:

a. 24 ÷ 3 = 8 ⇒ i. 8 × 3 ÷ (6 − 3) = 8

b. 53 × 7 = 371 ⇒ h. (8 × 7 − 3) × 7 = 371

g. 8 × (5 × 12 − 10) = 400 ⇒ f. 8 × 50 = 400

Explanation:

Given:

We have to match the equivalent expressions:

a. 24 ÷ 3 f. 8 × 50

b. 53 × 7 g. 8 × (5 × 12 − 10)

c. 56 − 21 h. (8 × 7 − 3) × 7

d. 4 − 3 i. 8 × 3 ÷ (6 − 3)

e. 40 × 2

Solution:

a. 24 ÷ 3 = 8

b. 53 × 7 = 371

c. 56 − 21 = 35

d. 4 − 3 = 1

e. 40 × 2 =80

f. 8 × 50 = 400

g. 8 × (5 × 12 − 10) Using PEMDAS rule.


8* (60-10)


8* 50


400

h. (8 × 7 − 3) × 7


(56-3)* 7


(53)* 7


371

i. 8 × 3 ÷ (6 − 3) = 8


(8* 3)/(3)


(24)/(3)


8

Answers:

a. 24 ÷ 3 = 8 ⇒ i. 8 × 3 ÷ (6 − 3) = 8

b. 53 × 7 = 371 ⇒ h. (8 × 7 − 3) × 7 = 371

g. 8 × (5 × 12 − 10) = 400 ⇒ f. 8 × 50 = 400

c,d and e didn't have any match

a is equivalent to i,b equivalent to h and g is equivalent to f.

User Milad
by
6.0k points